DISMANTLING SOCIAL NORMSAS PORTRAYED IN JAMES PURDY’SDON’T CALL ME BY MY RIGHT NAME - SYAM, ESSY; SYAMSIDAR, R.; ROSALIZA, MITA (Human Sustainability Procedia, 2018)
Social norm is created to control society and to make sure thatn it runs well parallel to morality and social system. Thus, the social norms are kept existing because they are considered good and they are, the, are treated as guidances for people’s lives. Anyway, in the process of humans’ development, certain social norms may no longer be considered applicable since they do not fit certain people’s thought/s. Responding to this situation, people express theirunsatisfaction with the existed norm through various media. One of the media is literary work. Related to that, this writing analyzes how a literary work, James Purdy’sDon’t Call Me By My Right Namedismantles social norms in American society.